Real-world data on efficacy and safety of obinutuzumab plus chlorambucil, rituximab plus chlorambucil, and rituximab plus bendamustine in the frontline treatment of chronic lymphocytic leukemia: The GO-CLLEAR Study by the Czech CLL Study Group - Panovská, Anna; Němcová, Lucie; Nekvindová, Lucie; Špaček, Martin; Šimkovič, Martin; Papajík, Tomáš; Brejcha, Martin; Lysák, Daniel; Zuchnická, Jana; Novák, Jan; Starostka, David; Poul, Hynek; et al. (Hematological oncology, 2020)
Until recently, a combination of anti-CD20 antibody plus less intensive chemotherapy was a standard of care in elderly population with previously untreated chronic lymphocytic leukemia (CLL). The aim of this observational study was to retrospectively assess efficacy and safety of obinutuzumab + chlorambucil (G-Clb), rituximab + chlorambucil (R-Clb), and bendamustine + rituximab (BR) given as the frontline therapy within routine practice. The final analyzed dataset included 398 consecutive CLL patients from 10 hematology centers cooperating within the Czech CLL Study Group: 63 treated with G-Clb, 78 with R-Clb, and 257 with BR. There were no significant differences in prognostic and predictive markers among the groups. On the contrary, median age at the start of therapy and cumulative illness rating scale (CIRS) score was significantly higher in R-Clb group. Obinutuzumab plus chlorambucil regimen was preferably offered to elderly patients (compared to BR) with less severe comorbidities and lower CIRS score (compared to R-Clb). A time period when a treatment was indicated had also a strong impact on the choice of the regimen. The overall response rate reached 76% (30% complete remissions, CRs) in G-Clb, 75% (22% CRs) in R-Clb, and 85% (47% CRs) in BR group. Median event-free survival was 49.0 months for G-Clb, 20.3 months for R-Clb, and 37.0 months for BR group. Neutropenia grade ≥ 3 developed in 43% of G-Clb, 31% of R-Clb and in 49% of BR patients, grade ≥ 3 infections were recorded in 17% of G-Clb, 6.4% of R-Clb, and 17% of BR patients. In conclusion, real-world therapeutic activity of G-Clb appears to be at least comparable to prospective clinical trial data. R-Clb yields relatively good results in very old and severely comorbid patients.
Keywords: rituximab-bendamustine; chlorambucil; mužské pohlaví; míra přežití; Retrospective Studies; Chlorambucil; Male; chronická lymfatická leukemie; senioři; senioři nad 80 let; retrospektivní studie; Remission Induction; rituximab-chlorambucil; Female; Humans; Prognosis; rituximab; CLL; Antibodies, Monoclonal, Humanized; Bendamustine Hydrochloride; CIRS; následné studie; lidé; Follow-Up Studies; Middle Aged; ženské pohlaví; lidé středního věku; obinutuzumab-chlorambucil; Rituximab; Antineoplastic Combined Chemotherapy Protocols; bendamustin hydrochlorid; prognóza; Aged, 80 and over; frontline treatment; Leukemia, Lymphocytic, Chronic, B-Cell; protokoly protinádorové kombinované chemoterapie; indukce remise; Survival Rate; humanizované monoklonální protilátky; Aged